BANJIR BANDANG DI DAS GARANG JAWA TENGAH (PENYEBAB, DAN IMPLIKASI) - , Purwadi Suhandini, Drs.,SU. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study of flash flood was conducted in Garang River Basin, Semarang, Central Java, Indonesia. The aim of this research are: 1) to study the characteristics of the flash flood in the Garang River Basin